2014
DOI: 10.1371/journal.pone.0104153
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Magnitude of Impaired Cutaneous Sensation across the Hand in the Chronic Period Post-Stroke

Abstract: Sensation is commonly impaired immediately post-stroke but little is known about the long-term changes in cutaneous sensation that have the capacity to adversely impact independence and motor-function. We investigated cutaneous sensory thresholds across the hand in the chronic post-stroke period. Cutaneous sensation was assessed in 42 community-dwelling stroke patients and compared to 36 healthy subjects. Sensation was tested with calibrated monofilaments at 6 sites on the hand that covered the median, ulnar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…[7][8][9] This is despite the fact that the prevalence of somatosensation deficits poststroke (which includes proprioception and cutaneous sensation) ranges from 33 to 65%. [10][11][12] These deficits are mainly caused by damage to the primary somatosensory cortex which results in the inability to perceive, process, and interpret sensory feedback. This leads to altered motor responses which contribute further to abnormal sensory feedback creating a vicious cycle resulting in balance impairment.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] This is despite the fact that the prevalence of somatosensation deficits poststroke (which includes proprioception and cutaneous sensation) ranges from 33 to 65%. [10][11][12] These deficits are mainly caused by damage to the primary somatosensory cortex which results in the inability to perceive, process, and interpret sensory feedback. This leads to altered motor responses which contribute further to abnormal sensory feedback creating a vicious cycle resulting in balance impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining sensation of the hand is important for fine motor control, prevention of injury, and quality of life. 25 The 2PD test serves as a reliable measure of sensory tactile function and is associated with nerve integrity following injury and/or surgery. 26 In the current study, we found static 2PD was influenced by age, mechanism of amputation, and level of amputation (Table 3, P < .05).…”
Section: Resultsmentioning
confidence: 99%
“…34 The AsTex® is a rectangular plastic board to measure edge detection capabilities, with parallel vertical ridges and grooves that logarithmically reduce in width and are printed on a specific test area laterally across the board. The errors that can occur due to changes in force applied by the index finger on the board or the velocity with which the finger is moved 35 were overcome by placing the AsTex® board on the SITAR table, which can sense the touch force and position on the AsTex® board. To assess the tactile resolution, participants placed their index finger on the rough end of the AsTex® board, which was slid slowly along the board by a therapist until the point where the surface started to feel smooth to the subject.…”
Section: Resultsmentioning
confidence: 99%